The presence of the Y-chromosome, not the absence of the second X-chromosome, alters the mRNA levels stored in the fully grown XY mouse oocyte. - Baozeng Xu; Yayoi Obata; Feng Cao; Teruko Taketo (PLoS ONE, 2012)
The oocytes of B6.Y(TIR) sex-reversed female mouse mature in culture but fail to develop after fertilization because of their cytoplasmic defects. To identify the defective components, we compared the gene expression profiles between the fully-grown oocytes of B6.Y(TIR) (XY) females and those of their XX littermates by cDNA microarray. 173 genes were found to be higher and 485 genes were lower in XY oocytes than in XX oocytes by at least 2-fold. We compared the transcript levels of selected genes by RT-PCR in XY and XX oocytes, as well as in XO oocytes missing paternal X-chromosomes. All genes tested showed comparable transcript levels between XX and XO oocytes, indicating that mRNA accumulation is well adjusted in XO oocytes. By contrast, in addition to Y-encoded genes, many genes showed significantly different transcript levels in XY oocytes. We speculate that the presence of the Y-chromosome, rather than the absence of the second X-chromosome, caused dramatic changes in the gene expression profile in the XY fully-grown oocyte.